Coherence in resonance fluorescence - Xu-Jie Wang; Guoqi Huang; Ming-Yang Li; Yuan-Zhuo Wang; Li Liu; Bang Wu; Hanqing Liu; Haiqiao Ni; Zhichuan Niu; Weijie Ji; Rongzhen Jiao; Hua-Lei Yin; et al. (Nature Communications)
Abstract Resonance fluorescence of a two-level emitter displays persistently anti-bunching irrespective of the excitation intensity, but inherits the driving laser’s linewidth under weak monochromatic excitation. These properties are commonly explained in terms of two disjoined pictures, i.e., the emitter’s single photon saturation or passively scattering light. Here, we propose a unified model that treats all fluorescence photons as spontaneous emission, one at a time, and can explain simultaneously both the spectral and correlation properties of the emission. We theoretically derive the excitation power dependencies, measurable at the single-photon incidence level, of the first-order coherence of the whole resonance fluorescence and super-bunching of the spectrally filtered, followed by experimental confirmation on a semiconductor quantum dot micro-pillar device. Furthermore, our model explains peculiar coincidence bunching observed in phase-dependent two-photon interference experiments. Our work provides an intuitive understanding of coherent light-matter interaction and may stimulate new applications.